ASPEK-ASPEK PENYEBAB KESULITAN MENULIS PUISI PADA SISWA KELAS V SEKOLAH DASAR - Ervina Septiwi; Eko Kuntarto; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the types of difficulties students face in writing poetry in fifth grade elementary school, the causes of these difficulties, and the strategies implemented by teachers to address students' challenges in writing poetry. This research was conducted at SD Negeri 110/I Tenam from August 9, 2024, to September 9, 2024. The researchers used a qualitative approach with a case study research type. The research respondents are the students of class VB and the teacher of class VB at SD Negeri 110/I Tenam. The data collection methods in this research are observation, questionnaires, and interviews. The results of this research reveal the types of difficulties students face in writing poetry, namely: difficulties in formulating ideas/themes, difficulties in arranging vocabulary, difficulties in creating figurative sentences, difficulties in using rhyme, and difficulties in the structure of poetry writing. The causes of students experiencing difficulties in writing poetry can be attributed to two factors: internal factors, which include a lack of understanding of poetry writing, insufficient language skills, a lack of practice in writing poetry, and a lack of motivation to write poetry. Meanwhile, external factors include conventional teaching methods, less engaging learning media, underutilization of libraries, and a lack of support from the family environment. The strategies implemented by teachers to address students' difficulties in writing poetry are: providing motivation to students, offering poetry writing exercises, and guiding students in learning how to write poetry.